Satellite communication engineering - Kolawole, Michael O. (CRC Press, 2014)
This rich guide to satellite communication engineering includes recent developments enabling digital information transmission and delivery via satellite. This book takes a thorough approach to ramping-up the reader in the topical foundations. Throughout, concepts are developed on an intuitive, physical basis, with further derivations provided using applications and performance curves. Now thoroughly updated, this edition covers satellite and earth station design, antenna tracking, links and communications systems, error detection and correction and regulations and procedures for system modeling, integration, testing and evaluation--